1997
DOI: 10.1007/bf02447887
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiological characteristics of twinning in Northwest India

Abstract: Jammu, the average twinning rate over the period 1984-93 were 10.70 and 11.40 respectively. Stillbirth rate among twins was much higher in Gujjars as compared to other three samples. Regional trends of twinning rate showed the highest incidence in the state of Uttar Pradesh, while the lowest in Tamilnadu. There were no significant differences between states for MZ twinning rate, while differences in the DZ twinning rate were significant in some instances. Maternal age and parity specific twinning rate showed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…In the present study, the highest multiple birth rate was observed in a parity group of 4. Two studies in India also reported higher risks in high parities and the rate picked at parity of 4 (Rao, 1978; Sharma, 1997). Another study in India found a twinning rate of 6/1,000 deliveries among mothers with pregnancy order of 1 and the rate increased significantly to reach 19/1,000 in women with birth order of 4 or more (Satija et al, 2008).…”
Section: Discussionmentioning
confidence: 98%
“…In the present study, the highest multiple birth rate was observed in a parity group of 4. Two studies in India also reported higher risks in high parities and the rate picked at parity of 4 (Rao, 1978; Sharma, 1997). Another study in India found a twinning rate of 6/1,000 deliveries among mothers with pregnancy order of 1 and the rate increased significantly to reach 19/1,000 in women with birth order of 4 or more (Satija et al, 2008).…”
Section: Discussionmentioning
confidence: 98%
“…The DZ twinning was much higher than found in other Indian studies where analysis was done using Wienberg’s Differential method. [ 8 9 10 11 ] The number of like twins were 102 (68% – MZ-34, DZ-68) and unlike twins were 48 (32%). Using the Weinberg’s method in the present study, MZ can be calculated to 54 (36%) and DZ 96 (64%).…”
Section: Discussionmentioning
confidence: 99%
“…In the past many decades, there have been few epidemiological studies involving twins in India. [ 8 9 10 11 12 ] Over the recent decades with the dynamicity of the populations between the rural and urban areas, the improvement in the health awareness associated with better education opportunities, improving birth rates, advancement in the urban lifestyle with progressive women employment and empowerment, the demographic trends in the society including the twin’s subgroup is also changing. [ 13 ]…”
Section: Introductionmentioning
confidence: 99%